Enabling the Unconstrained Epidermal Pulse Wave Monitoring via Finger‐Touching. (4th June 2021) - Wang, Xue; Yang, Jun; Meng, Keyu; He, Qiang; Zhang, Gaoqiang; Zhou, Zhihao; Tan, Xulong; Feng, Zhiping; Sun, Chenchen; Yang, Jin; Wang, Zhong Lin
Abstract: Unconstrained measurement of physiological signals including electrocardiograph, respiration, and temperature by sensors through incorporation into commonly used objects has sparked a notable revolution in healthcare monitoring. However, unconstrained precision epidermal pulse wave monitoring is rarely reported. Although the current flexible skin‐mounted sensors can capture pulse waves, they lack the capability to perceive tiny pulse pressure in an unconstrained manner. Herein, utilizing thin‐film materials and multilevel microstructure design, an ultrathin and flexible sensor (UFS) with the features of high flexibility, shape‐adaptability, and ultra‐broad‐range high pressure sensitivity is proposed for unconstrained precision pulse wave sensing. Given these compelling features, the UFS is mounted to the surfaces of commonly used objects and successfully detects the fingertip pulse wave even under an ultra‐broad‐range finger‐touching force. Key cardiovascular parameters are also extracted from the acquired fingertip pulse wave accurately. Furthermore, a proof‐of‐concept healthcare system, by combining the UFS and flexible devices (for example, flexible phones or E‐newspapers) is demonstrated, offering a great advancement in developing an all‐in‐one system for IoT‐based bio‐health monitoring at all times and places. Abstract : Multilevel microstructures consisting of hexagonal prisms and nanowires provide sufficient contact‐separation area and deformation space between the tribo‐pair, which endows the reported ultrathin and flexible sensor (UFS) with a high sensitivity, up to 0.15 mV Pa −1, even under a static force of 1500 mN. Given this superior performance, the UFS can capture fingertip pulse waves in an unconstrained manner via finger‐touching.